BENTUK DAN FUNGS I BAHASA RITUAL CA RU P AÑC A SAT A DI DENPASAR BARAT - Weja Apryanthi, Ni Putu (Humanis, 2015)
This study takes the object of the ritual Caru Pañca Sata (CPS) which is part of the ritual Bhuta Yadnya on Hindus in Bali. In this ritual used language that is typical Balinese or Kawi Bali, which is a mixture of Sanskrit, Old Javanese, Middle Javanese and Balinese New. Used to analyze the structural linguistic theory and the theory of functions of language. The methods and techniques used include 3 stages: the first stage is the provision of data by using the methods and techniques capable semuka see and record and record; The second is the stage of data analysis using descriptive analysis methods and techniques to direct element (BUL); The third is the stage of presenting the results of the use of formal and informal methods as well as deductive techniques. The results obtained from the analysis of the form: the form of the CPS language is a form of ritual puja saa. Elements that build the CPS ritual language is a morpheme consisting of a free morpheme and bound morpheme; word consisting of basic words and words that get invented a process mrfologis affixation, reduplication and compounding; phrase consisting of phrases and phrases endosentrik eksosentrik; clause consisting of free clauses and clause transitive verbal; sentence consisting of a single sentence, complex sentences and imperative sentences. The functions contained in the CPS ritual language is imaginative function, emotive function, the magical function.
Keywords: form, function, caru pañca sata